Marion takes a break - Barkley, Callie (Barkley, Callie. Critter Club., 2013)
When a broken ankle forces Marion to withdraw from the horse show, she finds a way to stay active by helping her friends at the Critter Club animal shelter find homes for a litter of kittens.